2019
DOI: 10.3390/w11020317
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Factors Affecting Pan Evaporation in the Haihe River Basin, China

Abstract: Pan evaporation (Epan) is an important indicator of regional evaporation intensity and degree of drought. However, although more evaporation is expected under rising temperatures, the reverse trend has been observed in many parts of the world, known as the “pan evaporation paradox”. In this paper, the Haihe River Basin (HRB) is divided into six sub-regions using the Canopy and k-means (The process for partitioning an N-dimensional population into k sets on the basis of a sample is called “k-means”) to cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…However, we showed that watershed-level ET had a significant decreasing trend in the QRB, coincident with previous studies [2,42]. This was in contrast to the global warming trend and ET was expected to increase under increasing air temperature in the study region [73][74][75]. Declines in ET have also been reported in the literature around the world, such as eastern China [76], Haihe River Basin [77], Liaohe River Delta [78], and the southern hemisphere in Africa [79].…”
Section: Effects Of Land Use and Land Cover Changes On All Et Componentssupporting
confidence: 88%
“…However, we showed that watershed-level ET had a significant decreasing trend in the QRB, coincident with previous studies [2,42]. This was in contrast to the global warming trend and ET was expected to increase under increasing air temperature in the study region [73][74][75]. Declines in ET have also been reported in the literature around the world, such as eastern China [76], Haihe River Basin [77], Liaohe River Delta [78], and the southern hemisphere in Africa [79].…”
Section: Effects Of Land Use and Land Cover Changes On All Et Componentssupporting
confidence: 88%
“…However, either data from advanced techniques that use sensors to measure evaporation are not yet easily available in developing countries, or the available data are not sufficient for statistical analyses and the development of equations. Pan evaporation is considered a reasonably good indicator of the regional evaporation intensity that is usually used for estimations of lake evaporation and water resource planning and management [14]. Pan evaporation and meteorological variables, including solar radiation, sunshine duration, atmospheric pressure, vapor pressure, wind velocity, air temperature, and relative humidity, were used in a study on lake evaporation by Yan et al [14].…”
Section: Methodsmentioning
confidence: 99%
“…Pan evaporation is considered a reasonably good indicator of the regional evaporation intensity that is usually used for estimations of lake evaporation and water resource planning and management [14]. Pan evaporation and meteorological variables, including solar radiation, sunshine duration, atmospheric pressure, vapor pressure, wind velocity, air temperature, and relative humidity, were used in a study on lake evaporation by Yan et al [14]. A monthly pan evaporation dataset was used for monitoring and estimating important aspects of evaporation in various parts of the world [11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations